Analysing morphogenetic design approaches in the context of hypothetical housing examples - Anday Türkmen (Journal of Design for Resilience in Architecture and Planning)
Conceptual approaches that systematically integrate ecological reasoning with algorithmic design processes have gained increasing attention in theoretical discussions on architectural practice. However, a significant gap remains in terms of their application, particularly within the context of housing architecture. In response to this theoretical gap, this study aims to evaluate the algorithmic orientations of designers who transform their spatial inquiries into an ecological organization through hypothetical housing examples. This evaluation is framed through the concept of morphogenetic design—a biologically informed architectural approach in which form and space evolve not through predetermined templates but through generative, adaptive, and systemic processes. Accordingly, the study addresses two main research questions: 'The potential impact of morphogenetic design on residential buildings' and 'Integration of morphogenetic design into housing construction processes'. The study employed a qualitative research design and the literature review method to answer the research questions. The research sample consists of four hypothetical housing projects: Embryological House, Multistory Apartment Building, Molecular Engineered House, and The Fab Tree Hab. These projects were developed using morphogenetic design approaches in 2000 and beyond. In order to collect data from the main mass in an easy and fast way, Homogeneous sampling method, one of the purposeful sampling types, was preferred. In this context, the 'descriptive content analysis method' was preferred to analyse the data obtained in the research and the data was analysed in two stages. In the first stage, descriptive analysis was carried out and the general trend was determined by examining the qualitative studies that could answer the research questions. In the second stage, content analysis was carried out and the data obtained were organised and interpreted according to the parameters set by the researcher. The analysis indicates that morphogenetic design has the capacity to substantially transform the formal, functional and ecological dimensions of future residential buildings. Digital design methods, biologically inspired production techniques and user-participatory design strategies have rendered it feasible for buildings to self-renew, establish symbiotic relationships with their environment and adapt to various living scenarios. This process is characterised by the integration of sustainability and user experience across multiple stages, ranging from design to construction.